Real‐world experience with direct brain‐responsive neurostimulation for focal onset seizures - Razavi, Babak (Epilepsia, 2020)
OBJECTIVE: The RNS System is a direct brain‐responsive neurostimulation system that is US Food and Drug Administration–approved for adults with medically intractable focal onset seizures based on safety and effectiveness data from controlled clinical trials. The purpose of this study was to retrospectively evaluate the real‐world safety and effectiveness of the RNS System. METHODS: Eight comprehensive epilepsy centers conducted a chart review of patients treated with the RNS System for at least 1 year, in accordance with the indication for use. Data included device‐related serious adverse events and the median percent change in disabling seizure frequency from baseline at years 1, 2, and 3 of treatment and at the most recent follow‐up. RESULTS: One hundred fifty patients met the criteria for analysis. The median reduction in seizures was 67% (interquartile range [IQR] = 33%‐93%, n = 149) at 1 year, 75% (IQR = 50%‐94%, n = 93) at 2 years, 82% (IQR = 50%‐96%, n = 38) at ≥3 years, and 74% (IQR = 50%‐96%, n = 150) at last follow‐up (mean = 2.3 years). Thirty‐five percent of patients had a ≥90% seizure frequency reduction, and 18% of patients reported being clinically seizure‐free at last follow‐up. Seizure frequency reductions were similar regardless of patient age, age at epilepsy onset, duration of epilepsy, seizure onset in mesial temporal or neocortical foci, magnetic resonance imaging findings, prior intracranial monitoring, prior epilepsy surgery, or prior vagus nerve stimulation treatment. The infection rate per procedure was 2.9% (6/150 patients); five of the six patients had an implant site infection, and one had osteomyelitis. Lead revisions were required in 2.7% (4/150), and 2.0% (3/150) of patients had a subdural hemorrhage, none of which had long‐lasting neurological consequences. SIGNIFICANCE: In this real‐world experience, safety was similar and clinical seizure outcomes exceeded those of the prospective clinical trials, corroborating effectiveness of this therapy and suggesting that clinical experience has informed more effective programming.